2014
DOI: 10.1002/cbic.201402067
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Elements Distal to the Ligand Binding Pocket Modulate the Efficiency of a Synthetic Riboswitch

Abstract: Synthetic riboswitches can serve as sophisticated genetic control devices in synthetic biology, regulating gene expression through direct RNA-ligand interactions. We analyzed a synthetic neomycin riboswitch, which folds into a stem loop structure with an internal loop important for ligand binding and regulation. It is closed by a terminal hexaloop containing a U-turn and a looped-out adenine. We investigated the relationship between sequence, structure, and biological activity in the terminal loop by saturatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Thus, depriving A17 of the Hoogsteen edge hydrogen acceptors should lead to breaking of the G5–A17 contact and diminishing riboswitch activity. Indeed, the A17C riboswitch mutant shows reduced gene regulatory activity against NEO ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, depriving A17 of the Hoogsteen edge hydrogen acceptors should lead to breaking of the G5–A17 contact and diminishing riboswitch activity. Indeed, the A17C riboswitch mutant shows reduced gene regulatory activity against NEO ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…During an in vivo screen of a neomycin riboswitch library with a randomized apical hexaloop (nt 13-18), sequences with a U to C mutation at position 14 were identified as functional despite their apparent deviation from the structurally important U-turn consensus sequence ( Fig. 1C; Weigand et al 2014). However, compared to the WT riboswitch, their regulatory power is slightly diminished.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent screen aimed at identifying functional sequence variants of the apical loop of the neomycin riboswitch, we found that a replacement of U14 by a C residue ( Fig. 1A) also results in functional riboswitches (Weigand et al 2014). Such a mutation should interfere with the proper folding and the stability of the U-turn motif because C lacks an imino proton and is thus not able to form a hydrogen bond analogous to the one between the U imino group and the phosphate backbone in the canonical U-turn motif.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently 20 injections of 2.0 μl at a 180 s interval were made. The sample cell was stirred with a speed of 750 rpm (60). The software NITPIC was used to integrate the injection peaks to yield the associated heat for each injection (61,62), the experimental binding isotherm was subsequently plotted and the curve fit with a one-site binding model using the software SEDPHAT (63).…”
Section: Methodsmentioning
confidence: 99%